Foreign body aspiration: What is the outcome? - YILDIZELİ, BEDRETTİN; KARADAĞ, BÜLENT TANER (WILEY-LISS, 2002)
Undiagnosed and retained foreign bodies may result in serious complications such as pneumonia, atelectasis, or bronchiectasis. We reviewed a total of 174 children with foreign body aspiration (FBA). Clinical, radiological, and bronchoscopic findings of these patients were evaluated according to the nature of foreign body and elapsed time from aspiration to diagnosis. Significant differences were noted between patients with organic and inorganic FBA in terms of clinical and radiological findings. Cough, recurrent pneumonia, and fever were the most common presenting symptoms in patients with delayed diagnosis. Long-term follow-up was available for 110 patients for a mean duration of 37.8 +/- 23.7 months (range, 1-88 months). We evaluated the course of recovery after bronchoscopic removal. Organic FBA was of comparable duration as for inorganic FBA, and prolonged follow-up was associated with increased risk of persistent symptoms and bronchiectasis (P < 0.001). The risk of long-term complications increased with increasing elapsed time from aspiration to diagnosis; complications were as high as 60% in children who were diagnosed 30 days after FBA (P = 0.0035). Bronchiectasis was a major complication, found in 25% of patients whose diagnosis was delayed by more than 30 days (P = 0.0001). Three patients with bronchiectasis underwent lobectomy. Patients with persistent asthma-like symptoms such as cough and wheezing required treatment with inhaled corticosteroids and bronchodilators. The positive response to this treatment was thought to be a confirmation of the development of transient bronchial hyperresponsiveness induced by foreign bodies. We conclude that timely diagnosis and appropriate treatment of FBA is important to prevent long-term complications in affected children. (C) 2002 Wiley-Liss, Inc.
Keywords: foreign body aspiration; children; long-term complications; bronchial hyperresponsiveness; pneumonia; atelectasis; bronchiectasis; wheezing; BODIES; CHILDREN; COMPLICATIONS; DIAGNOSIS